Declining health status of Brown Skua (Stercorarius antarcticus lonnbergi) parents and their offspring during chick development - Ibañez, Andres Esteban; Graña Grilli, Maricel; Figueroa, Amalia; Pari, Marcela; Montalti, Diego (Polar Biology)
During breeding, Brown Skuas (Stercorarius antarcticus lonnbergi) perform a great physical effort in the care and maintenance of the nest. Interestingly, the breeding colony on which this work was conducted is in steady decline in recent years. In order to understand the physiological background responsible for the trade off between reproductive effort and health status, in adults and the possible reasons for the colony decline, we evaluated the health status in Brown Skuas parents and growing chicks and blood samples were obtained in three different breeding stages from adults: In (incubation), Er (after egg hatching), and Lr (during chick rearing) and from developing chicks. Serum albumin, α-, β-. and γ-globulin fractions, IgY level and corticosterone were determined in adults, while plasma proteins concentration, electrolytes, and γ-globulins were determined in chicks. Differences in albumin, α-, and γ-globulins and IgY levels were observed in adults through the reproductive stages, indicating a decline in nutritional status and immunocompetence during breeding. In addition, a decline in body condition and immune status was observed in growing chicks, indicating a close relationship between the decrease of the health status and reproductive effort performed by adults and the physiological status of the nestlings during development. Fil: Ibañez, Andres Esteban. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de la Plata. Facultad de Ciencias Naturales y Museo. División Zoología de Vertebrados. Sección Ornitología; Argentina Fil: Graña Grilli, Maricel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigaciones en Biodiversidad y Medioambiente. Universidad Nacional del Comahue. Centro Regional Universidad Bariloche. Instituto de Investigaciones en Biodiversidad y Medioambiente; Argentina Fil: Figueroa, Amalia. Provincia de Buenos Aires. Hospital Interzonal General de Agudos ...